Human health impacts of exposure to phthalate plasticizers: An overview of reviews. (January 2022) - Eales, J.; Bethel, A.; Galloway, T.; Hopkinson, P.; Morrissey, K.; Short, R.E.; Garside, R.
Abstract: In this review of reviews, we overview the current global body of available evidence from structured reviews of epidemiological studies that explore human health outcomes associated with exposure to phthalates (chemical plasticisers commonly found in plastics). We found robust evidence for an association with lower semen quality, neurodevelopment and risk of childhood asthma, and moderate to robust evidence for impact on anogenital distance in boys. We identified moderate evidence for an association between phthalates/metabolites and low birthweight, endometriosis, decreased testosterone, ADHD, Type 2 diabetes and breast/uterine cancer. There was some evidence for other outcomes including anofourchette distance, fetal sex hormones, pre-term birth, lower antral follicle count, reduced oestrodiol, autism, obesity, thyroid function and hearing disorders. We found no reviews of epidemiological human studies on the impact of phthalates from recycled plastics on human health. We recommend that future research should use urine samples as exposure measures, consider confounders in analyses and measure impacts on female reproductive systems. Our findings align with emerging research indicating that health risks can occur at exposure levels below the "safe dose" levels set out by regulators, and are of particular concern given potential additive or synergistic "cocktail effects" of chemicals. This raises important policy and regulatory issues for identifying and controlling plastics and health related impacts and highlights a need for more research into substances of concern entering plastics waste streams via recycling.